2021
DOI: 10.1002/joc.7218
|View full text |Cite
|
Sign up to set email alerts
|

The drivers of extreme rainfall event timing in Australia

Abstract: Australia experiences some of the world's most variable rainfall. Previous studies have mostly focused on understanding rainfall variability in terms of frequency and intensity. However, understanding the timing of when extreme rainfall occurs is crucial for seasonal prediction, although it largely remains unexplored. Here we investigate the timing of extreme rainfall in Australia and the spatial variability of this timing. This study examines how some of the large-scale drivers, such as the El Niño-Southern O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 65 publications
(112 reference statements)
4
10
1
Order By: Relevance
“…In all three regions there is clear seasonality to rain intensity, with the T1 and tercile 2 (T2 hereafter) days showing relatively even distribution throughout the year and a stronger skew toward the Southern Hemisphere summer months (November to February) as the rain intensity increases. That is to say, the greatest number of T3 and top 100 days occur in the tropical wet season (DJF) for Darwin (in agreement with the findings of Dey et al (2021), who found, using AWAP, that extreme rainfall in northern Australia usually occurs in austral summer), and the summer months (NDJF) for both Brisbane and Melbourne. This latter result is in contrast to Dey et al (2021), who found that in southern Australia extreme rainfall usually occurs in the autumn and winter months, but that the timing is highly variable and that in southeastern Australia extreme rainfall can fall at any time of the year.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…In all three regions there is clear seasonality to rain intensity, with the T1 and tercile 2 (T2 hereafter) days showing relatively even distribution throughout the year and a stronger skew toward the Southern Hemisphere summer months (November to February) as the rain intensity increases. That is to say, the greatest number of T3 and top 100 days occur in the tropical wet season (DJF) for Darwin (in agreement with the findings of Dey et al (2021), who found, using AWAP, that extreme rainfall in northern Australia usually occurs in austral summer), and the summer months (NDJF) for both Brisbane and Melbourne. This latter result is in contrast to Dey et al (2021), who found that in southern Australia extreme rainfall usually occurs in the autumn and winter months, but that the timing is highly variable and that in southeastern Australia extreme rainfall can fall at any time of the year.…”
Section: Resultssupporting
confidence: 93%
“…This latter result is in contrast to Dey et al. (2021), who found that in southern Australia extreme rainfall usually occurs in the autumn and winter months, but that the timing is highly variable and that in southeastern Australia extreme rainfall can fall at any time of the year. This clear shift in the seasonality of rain intensity in all regions indicates that studying the settings of extreme rainfall events remains important for the prediction of extreme rainfall.…”
Section: Resultscontrasting
confidence: 88%
See 3 more Smart Citations